PERINTAH BARU DALAM INJIL YOHANES - Ohoilulin, Marlond (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2012)
This paper is an exegetical effort to explore the novelty dimension of the New Commanment Jesus proclaimed in the Gospel of John, which is to love one another. Since early, such a command has been internalized and implemented within the Israelities. They are always asked to love their neighbours as they love themselves. Jesus repromulgates this command to His disciples. Thus, we might ask, what exactly the novely of the command to love one another?